Systematics of the Vanilla chamissonis clade (Orchidaceae): a study based on integrative taxonomy - Pansarin, Emerson R. (Plant ecology and evolution, 2025)
Background and aims – The Brazilian biomes include the world’s greatest diversity of Vanilla . This richness has required studies on species boundaries, as many taxa have been described or erroneously synonymized. This is the case for V. argentina , a species described from the Dry Chaco synonymized under V. chamissonis . While studying the diversity of Neotropical Vanilla , differences between plants from the Cerrado/Dry Chaco, the Atlantic Forest, and the Caatinga became evident. Material and methods – Descriptions of members of the Vanilla chamissonis clade, i.e. V. argentina , V. calyculata , and V. chamissonis are provided and a morphological comparison is given. An identification key and illustrations are provided. Geographic distributions and the reproductive strategies are presented. The phylogenetic relationships among the members of the V. chamissonis clade are discussed based on an ITS (nrDNA) phylogeny. Key results – Plants occurring in the Cerrado and Dry Chaco correspond to V. argentina , while V. calyculata and V. chamissonis occur in dry environments and in the Atlantic Forest, respectively. Vanilla argentina is distinguished from the other species by several characteristics, such as the size of the leaves and the flower structures, and fruit features. Vanilla argentina is self-compatible, while V. calyculata and V. chamissonis have a reproductive system based on late-acting self-sterility. All three species are assessed as Endangered. The identities of V. carinata , V. gardneri , and V. vellozii are clarified. The name V. argentina is revalidated. Conclusion – The evaluation of vegetative and reproductive characteristics of both living and dried specimens is crucial to understand the species delimitation among Vanilla . All evidence reveals that V. argentina is distinct from V. chamissonis . Vanilla chamissonis is endemic to Brazil, while V. argentina is distributed throughout Brazil, Argentina, and Paraguay. Vanilla calyculata occurs in dry regions of South and Central Americas. The Vanilla chamissonis clade comprises a lineage of three species within the Vanilla pompona group.